MAKNA ESTETIKA ORNAMEN GEREJA GANJURAN, BAGI INKULTURASI RELIGI KULTUR JAWA - Anselmus Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2021)
Culture and religion can clash and can complement each other. Likewise, Javanese traditions and Church teachings can clash and weaken each other, but they can also complement and support each other. Aesthetics as part of culture can help or obscure the search for the Divine. The feelings and feelings of Javanese people who are so attached to culture often feel longing to find pieces of culture in worship. Efforts to represent the Divine Hyang through ornaments that are closely related to culture are not easy things, inviting problems from both; cultural and religious issues. Religious dogma sometimes forces its adherents to leave the culture. The uprooting of the culture and the compulsion to use other cultures in religious rituals often lead to a deep longing to live in and live the culture that has been abandoned and manifested in worship. The longing to live in and live Javanese culture for Catholics may be cured by the construction of the Church of the Sacred Heart of the Lord Jesus Ganjuran. The church with Javanese cultural ornaments was built with the aim of presenting Hyang Divine in Javanese culture; living Javanese culture with a Catholic breath. But whether all Catholics who worship in the HKTY Church can understand and develop their faith to the fullest. From observations and interviews with priests, parish councils, and parishioners, the majority of pilgrims are to the Sacred Heart of Jesus temple, not to the church. Many people from other places are attracted to the church to attend worship not because of the ornaments, but because of the rituals. People from other parishes come when there are certain events with worship using Javanese culture. From the research that used a questionnaire, more than 80% of the people were greatly helped in their relationship with Hyang Divine by using Javanese cultural ornaments. This research shows that the faith of the people is greatly helped by the presence of the HKTY Ganjuran church. Inculturation which aims to reconcile culture and liturgy is well established, enriching each other. The people's longing to meet the Divine Hyang using the culture that has "contained and gave birth" is fulfilled. On the other hand, with a good understanding, the presence of the HKTY Ganjuran church shows that culture and religion can go hand in hand and enrich each other. With a wise understanding, placing ornaments in faith properly and correctly according to the norms and orthodoxy correctly, the Church has strengthened its roots in Javanese culture without losing its identity.